Carcinoma of male breast: A rare case report from north east India with review of literature - Hazarika, Devid; Barua, Partha Pratim; Barman, Bhupen (Indian Journal of Case Reports, 2019)
Male breast cancer is a rare entity and accounts for 1% of all breast cancer cases with an average age of onset 67 years. Several risk factors have been identified, such as genetic and hormonal abnormalities. Even though more data is emerging about this disease, the poor level of awareness often results in late presentation and delayed diagnosis in our country. The present study reported the case of a 63 year old man who was diagnosed with an advanced invasive ductal carcinoma without any important risk factors. The case is presented for the rarity and to discuss awareness, regarding early diagnosis and proper management.